Tourism Development Strategy Analysis at the Dieng Plateau in Banjarnegara Regency - Prabawani, Gigit; Pudjianto, Hary; Setiasih, Endang (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
This study aims to describe the strategy of tourism development at the Dieng Plateau In Banjarnegara Regency, using indicators strengths, weaknesses, opportunities and threats. This research was conducted in Banjarnegara Regency tourism offices and tourist attractions at the Dieng Plateau In Banjarnegara Regency. This research target is, manager of Dieng Plateau tourist attraction, the tourism agencies and tourists. This research method using descriptive qualitative research method. Technique data collecting by interview, observation and documentation. Data analysis using the SWOT analysis, while the focus of his research studies are using the indicators of tourism planning, tourism promotion and tourism products. The research shows that still need for evaluation and better coordination of government, private sector and communities, tourism facilities and infrastructure still needs to be improved, the campaign still needs to be done effectively on the target market for tourism, and the development and improvement of tourism products include attractions, accessibility and existing tourist facilities. While the barriers to tourism development at the Dieng Plateau In Banjarnegara Regency is funding limitations, because the Department of Tourism is not given the authority to process the proceeds from tourism itself.